A semi-structured questionnaire survey of laboratory animal rehoming practice across 41 UK animal research facilities - Skidmore, Tess (PLoS One, 2020)
If a laboratory animal survives an experiment without lasting compromised welfare, its future must be negotiated. Rehoming may be a consideration. This paper reports on research findings that provide an indication of the uptake of animal rehoming by UK facilities and the associated moral, ethical, practical and regulatory considerations that inform decisions to rehome or not. This research addresses a widely acknowledged gap in the literature to understand both the numbers, and types of animals rehomed from UK research facilities, as well as the main motivations for engaging in the practice, and the barriers for those facilities not currently rehoming. From the ~160 UK research facilities in the UK, 41 facilities completed the questionnaire, giving a response rate of approximately 25%. Results suggest rehoming occurs routinely, yet the numbers are small; just 2322 animals are known to have been rehomed between 2015–2017. At least 1 in 10 facilities are rehoming. There exists a clear preference for the rehoming of some species (mainly cats, dogs and horses) over others (rodents, agricultural animals and primates). Indeed, although 94.15% of species kept in laboratories are rodents, they make up under a fifth (19.14%) of all animals known to be rehomed between 2015–2017. The primary motivation for rehoming is to boost staff morale and promote a positive ethical profile for the facility. Barriers include concern for the animal’s welfare following rehoming, high scientific demand for animals that leaves few to be rehomed, and, finally, certain animals (mainly those genetically modified) are simply unsuited to rehoming. The findings of this research will support facilities choosing to rehome, as well as those that are not currently engaging in the practice. By promoting the practice, the benefits to rehoming in terms of improving laboratory animal’s quality of life, helping facility staff to overcome the moral stress of killing, and addressing public concern regarding the fate of laboratory animals, can be attained. It is only once an understanding of rehoming from the perspective of UK research facilities has been ascertained, that appropriate policy and support can be provided.